Analisis Pembiayaan Murabahah Dalam Meningkatkan Usaha Mikro Kecil Dan Menegah Di Kelurahan Pekan Tanjung Pura Kecamatan Tanjung Pura Kabupaten Langkat - Nur Zukhairi Syafitri (Al-Sharf: Jurnal Ekonomi Islam, 2022)
This research aims to find out the increase in business of Small and Medium Enterprises (MSMEs) in Pekan Tanjung Pura Village, Tanjung Pura District, Langkat Regency, for murabahah financing carried out from Islamic Bank. The research method used is a qualitative research method that is descriptive with an empirical approach. The results of the study explained that the procedure and realization of murabahah financing carried out by MSME actors in Pekan Tanjung Pura Village, Tanjung Pura District, Langkat Regency consists of several stages, namely the stage of applying for financing, the file verification stage and analysis of financing feasibility, the approval and implementation stage of the contract and the stage of disbursement of financing. There was an increase in the business of MSME actors in Pekan Tanjung Pura Village, Tanjung Pura District, Langkat Regency after financing murabahah from Islamic Bank. Murabahah financing is used to increase capital in the form of goods and materials for business. Murabahah financing carried out helps the customer's business cycle continue to run, as well as help increase sales turnover. The obstacles faced by Islamic Banks in increasing Small Micro Enterprises in Tanjung Pura Week Village are: lack of public knowledge about Islamic Banks, accustomability to using conventional banks, lack of public attention to usury practices, and the distance of Islamic Banks.